ELEMENTAL ANALYSIS OF CARBOXYL-MODIFIED COPPER PHTHALOCYANINE PIGMENT - Nuritdinov, Abdullazizbek; Yusupov, Muzafar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents the elemental analysis results of copper phthalocyanine (CuPc–COOH) pigment modified with carboxyl functional groups. Using CHNS-O analysis, atomic absorption spectroscopy, and X-ray photoelectron spectroscopy (XPS), the percentages of C, H, N, O, and Cu elements in the pigment were determined. The results indicate that the carboxyl groups were successfully introduced into the pigment structure, leading to increased molecular polarity while maintaining the stability of the metal–ligand complex. The elemental analysis also made it possible to evaluate how the introduced functional groups influence the pigment’s physicochemical properties and its chemical integration capability with polymer binders.